Objectification of Women in the Film Women from Rote Island (2023) - Jhosheline, Jhosheline (Journal Research of Social Science, Economics, and Management, 2026)
Film as a cultural product functions not only as entertainment but also as a representational practice that constructs and reproduces social meanings. Women from Rote Island (2023) portrays women's experiences within an indigenous cultural context, particularly in relation to power relations, the female body, and gender-based violence. This study aims to analyze the representation of women in the film and the meanings constructed through its system of signs. This research adopts a constructivist paradigm with a qualitative descriptive approach. The method used was Roland Barthes' semiotic analysis, focusing on denotative, connotative, cultural–affective meanings, and myth. The research data consist of twelve film scenes selected purposively based on their relevance to issues of women's representation and gender relations. The analysis examines visual and narrative signifiers presented in these scenes. The findings reveal that at the denotative level, the film represents women's everyday life in an indigenous community as ordinary and natural. However, at the connotative level, women are constructed as vulnerable and subordinate subjects, while men are represented as socially authoritative actors. Cultural and affective dimensions reinforce this construction through the depiction of shame, fear, and resignation attached to female characters. At the level of myth, patriarchy and customary law are naturalized as legitimate social orders, positioning the objectification and violence against women as acceptable social consequences. This study concludes that Women from Rote Island not only reflects social reality but also actively reproduces patriarchal ideology through symbolic and affective representational practices.